ASSESSING THE KNOWLEDGE ABOUT WASTE MANAGEMENT IN NABARI PAYAM SOUTH SUDAN. A CROSS-SECTIONAL STUDY. - Agaar Chep Aboor; Mubiru , Deng; Sendagi , Mohammed (Student’s Journal of Health Research Africa, 2024)
Background In Uganda, management of waste within Team City is a challenge as reflected by 20.0 percent of total waste can only be collected and disposed of in Team City center and city divisions. The purpose of the study is to assess the knowledge about waste management in Nabari-Payam South Sudan. Methodology A cross-sectional survey, descriptive and explanatory design where quantitative and qualitative methods were adopted. A questionnaire and Focus group discussion were adopted and interviews for Key Informants. Data was analyzed descriptively using the Statistical Package for Social Sciences and thematic methods for quantitative and qualitative data. Results 207 (62.0%) disagreed about being trained on waste management, concerning knowledge about color coding segregation for waste, 267 (79.9%) of the respondents disagreed, About labeling the containers before filling them with waste, 146 (49.1%) agreed, the mean score was 3.40 and standard deviation 1.12 denoting that most of the respondents agreed about labeling containers before filling them with waste Concerning segregation of waste. Regarding the use of personal protective gear when handling waste, 104 (31.1%) strongly disagreed, the variable mean score and standard deviation were 2.31 and 1.15 respectively noting that there was disagreement on matters of use of protective gear. Conclusion Knowledge regarding waste management for residents of Nabari Payam was low due to the absence of training on matters of waste and its management from the local authorities. Recommendations Payam residents in Nabari Payam and the line ministries of the Republic of South Sudan should increase their budget allocations for waste management to train residents and managers at all levels and acquire adequate knowledge on waste collection, segregation, storage, transportation, and disposal tools.